2022
DOI: 10.1186/s12891-022-05358-x
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the lateral malleolus – a retrospective before-and-after study of treatment and resource utilization following the implementation of a structured treatment algorithm

Abstract: Background In 2015 a study of isolated lateral malleolar fractures (AO/OTA44-B1) treated at Sahlgrenska University hospital (SU) during two consecutive years revealed large-scale variation in the choice of treatment and planned follow-up. The study resulted in the development of a structured treatment algorithm (TA) for ankle fractures. We investigated the effects of this well-implemented TA on the classification, treatment and follow-up of lateral malleolar fractures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The most important nding of this long-term follow-up study is that treating stable ankle fractures nonsurgically is safe and does not lead to an increased risk of non-union, mal-union or increased reoperation rates. The current study builds upon the ndings of a previous study by Rydberg et al that demonstrated that implementing a standardised treatment algorithm for lateral malleolar ankle fractures led to a considerable decrease in surgical intervention (17). The present study can conclude that this approach is safe and reliable long term.…”
Section: Discussionsupporting
confidence: 72%
“…The most important nding of this long-term follow-up study is that treating stable ankle fractures nonsurgically is safe and does not lead to an increased risk of non-union, mal-union or increased reoperation rates. The current study builds upon the ndings of a previous study by Rydberg et al that demonstrated that implementing a standardised treatment algorithm for lateral malleolar ankle fractures led to a considerable decrease in surgical intervention (17). The present study can conclude that this approach is safe and reliable long term.…”
Section: Discussionsupporting
confidence: 72%
“…Ankle fractures are the third most common type of fracture, affecting both sexes and all age groups [ 1 3 ]. The spectrum of ankle fractures ranges from simple avulsions that can be safely treated non-surgically without follow-up to complex, open injuries that require multiple surgeries and long-term rehabilitation [ 4 ]. An increasing incidence of ankle fractures, especially in the elderly, has been reported in several studies over the past few years [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The low frequency of refractures might depend on advice on restrictions already given to children and their families, although if these restrictions are revised, it would be advisable to continuously follow the frequency of refractures to be able to detect any increase, and the SFR is a suitable tool for conducting this. 26 The current study has a number of strengths and limitations. The primary strength of the study is that it is based on a large cohort of more than 40,000 paediatric fractures with data from a population-based nationwide register that has been thoroughly validated and shown to have high coverage, completeness, and accuracy of registration.…”
Section: Discussionmentioning
confidence: 99%
“…The low frequency of refractures might depend on advice on restrictions already given to children and their families, although if these restrictions are revised, it would be advisable to continuously follow the frequency of refractures to be able to detect any increase, and the SFR is a suitable tool for conducting this. 26…”
Section: Discussionmentioning
confidence: 99%